A Holistic Needs Analysis for Developing Critical Reading Material to Enhance EFL Reading Proficiency - Lestari, Endah; Sukarni, Semi (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
This study delves into the development of critical reading material for English as a Foreign Language (EFL) reading classes through a comprehensive need analysis. Employing the Four D model encompassing defining, designing, developing, and disseminating, the research process unfolded in distinct phases. The initial phase involved a preliminary investigation at the English Language Education Department of Muhammadiyah Purworejo University to discern students' challenges within real-time learning contexts. Subsequently, a prototype of the needs analysis was formulated based on the findings from the preliminary study. Validation of this needs analysis occurred through consultation with two experts and field testing to ascertain the questionnaire's efficacy. The validation process revealed a high feasibility rate (85%) in assessing students' needs. Additionally, a preliminary field test involving 30 students from the English Language Education Department at Muhammadiyah Purworejo University was conducted to evaluate the questionnaire's practicality. The outcomes of the needs analysis served as a foundational framework for the development of critical reading materials, subsequently utilized in EFL reading classes.